Organochlorine and organophosphorous pesticides may induce colorectal cancer; A case-control study - Abolhassani, Moslem; Asadikaram, Gholamreza; Paydar, Parisa; Fallah, Hossein; Aghaee-Afshar, Mahmood; Moazed, Vahid; Akbari, Hamed; Moghaddam, Sodaif Darvish; Moradi, Afshin (Ecotoxicology and environmental safety, 2019)
Among the numerous agents, genetic factors and environmental elements such as pesticides have an important role in colorectal cancer (CRC) incidence. The present study aimed to investigate the probable-role of some organochlorine pesticides (OCPs) and organophosphorous pesticides (OPPs) in patients with CRC. In this case-control study, 42 patients with CRC and 30 healthy subjects were selected. The serum levels of some OCPs (α-HCH, β-HCH, γ-HCH, 2,4 DDE, 4,4 DDE, 2,4DDT and 4,4DDT) were measured by gas chromatography (GC) method. Serum levels of malondialdehyde (MDA), and total antioxidant capacity (TAC) as well as the enzyme activity of acetylcholinesterase (AChE) and arylesterase activity of Paraoxonase-1 (PON-1) were evaluated in all participants. The methylation specific PCR (MSP) assay was used for determining the methylation status of CpG island of p16 and MGMT genes in CRC patients. The mean serum levels of each OCPs were significantly higher in the patient group compared to the control group (P < 0.001). The AChE and arylesterase activity of PON-1 in the patient group were significantly lower than the control group (P < 0.001). The mean serum levels of MDA and TAC in the serum of the patient group were significantly higher than the control group (P < 0.001 and P < 0.002, respectively). The current findings demonstrated significantly hypermethylation of p16 promoter in CRC patients. Regarding the higher levels of OCPs in CRC patients, along with hypermethylation of the p16 promoter gene, diminishing in AChE and PON-1 activity and increasing in oxidative stress factors, the role of OCPs and OPPs in the CRC progression in the South-East of Iran may be assumed.